EFEKTIFITAS KEWENANGAN DINAS PERHUBUNGAN MENERBITKAN ANDALALIN BERDASARKAN PERATURAN MENTERI NOMOR 17 TAHUN 2021 - Resha Diah Yomeika; Edi Haskar; Fery Chofa (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The research background is that regional spatial planning is one of the problems in urban development today. The development of the city is quite fast with a fairly rapid population growth as well, so environmental issues are becoming an issue that is quite urgent in discussions about environmental sustainability for future generations. Spatial planning is important, so every province, city/regency must have rules that will guide spatial planning and become a reference for implementing development. the spatial planning of the city of Bukittinggi. The aim of the research is to find out the effectiveness of the authority of the Transportation Service in issuing Andalin Documents based on Ministerial Regulation Number 17 of 2021 concerning the Implementation of a Traffic Impact Analysis in the City of Bukittinggi and to find out what are the obstacles and efforts faced in the Effectiveness of the authority of the Transportation Service in issuing Andalin Documents. The research method used by the author is Juridical Empirical with descriptive analytical research specifications. Administrative arrangements have been effective, as evidenced by the developer before constructing the building he has applied for a building permit (IMB) to the Investment, One-Stop, Industry and Manpower Agency (DPMPTSPPTK). Constraints in the Effectiveness of the Authority of the Transportation Service in Issuing Andalan Documents Based on Ministerial Regulation Number 17 of 2021 concerning the Implementation of Traffic Impact Analysis in the City of Bukittinggi Certified consultants in Indonesia, especially in West Sumatra It is very rare because to get a reliable traffic analysis certificate you have to take a test held by held by the ministry of transportation, consultants and developers offer an agreement on the price of the Andalalin document, between the consultant and the developer the time the agreement for the completion of the Andalalin document is mostly not in accordance with the time promised or agreed, the developer sometimes carries out the construction first without taking care of a building permit (IMB) ) the developer should take care of the building permit (IMB) first and then carry out the construction. In its implementation it is less effective, because the recommendations in the Andalan document are not implemented by the developer. Examples include parking locations that are not accommodated (hotels/supermarkets)